Forty-eight-Week Safety and Efficacy On-Treatment Analysis of Ibalizumab in Patients with Multi-Drug Resistant HIV-1. (4th October 2017) - Emu, Brinda; Fessel, W Jeffery; Schrader, Shannon; Kumar, Princy N; Richmond, Gary; Win, Sandra; Weinheimer, Steven; Marsolais, Christian; Lewis, Stanley
Abstract: Background: Management of multi-drug-resistant (MDR) HIV-1 remains a challenge. The advent of antiretroviral (ARVs) with novel mechanisms of action are needed to expand therapeutic options for MDR patients. Ibalizumab (IBA) is a humanized monoclonal antibody with a unique binding specificity to the CD4 domain 2, allowing it to block viral entry into host cells without CD4 depletion. Patients completing the 24-week Phase 3 study (TMB-301) continued treatment in study TMB-311. Here, we report the durable efficacy and long-term safety of IBA with an optimized background regimen (OBR) through 48 weeks of treatment. Methods: TMB-301 was an open-label study investigating the antiviral activity and safety of IBA plus OBR in highly treatment-experienced patients with MDR HIV-1. Patients received an intravenous loading dose of 2, 000mg followed by 800mg doses every 2 weeks for 24 weeks. 7 days after loading dose, an OBR was added with at least 1 additional sensitive agent throughout the study. Following completion of the 24-week TMB-301 study, patients continued to receive IBA at 800mg every 2 weeks under TMB-311 for up to 48 weeks. Safety and efficacy were assessed until 48 weeks. Results: A total of 31 patients enrolled in TMB-301 completed the 24-week treatment period. Of 31 patients, 27 entered study TMB-311. These patients were highly resistant patients - 59% and 33% of patients had exhausted ≥3 and ≥4 ARV classes, respectively, and 7% of patients had HIV-1 resistant to all approved ARVs. IBA plus OBR was well tolerated. Of the 27 patients, 24 (89%) continued to receive treatment until Week 48. The three patients discontinued early due to non IBA-related reasons. No new or unexpected safety concerns emerged between Week 24 and 48. The potent suppression of viremia observed Week 24 was sustained through Week 48. Median viral load (VL) reduction from BL was 2.5 log10 at both Week 24 and 48. Of 27 patients (59%) 16 had VL <50 copies/ml and 17 (63%) patients had VL < 200 copies/ml. All 15 patients with VL < 50 copies/ml at Week 24 maintained viral suppression to Week 48. Conclusion: IBA plus OBR continued to achieve high rates of virologic suppression through Week 48. The results support the durable efficacy and long-term safety of IBA in highly treatment-experienced MDR patients and offer a valuable treatment option for patients. Disclosures: B. Emu, TaiMed Biologics: Employee and Shareholder, Salary; P. N. Kumar, TaiMed: Advisory Board and Investigator, Consulting fee and Grant recipient; G. Richmond, TaiMed: Investigator, Research support; S. Weinheimer, TaiMed: Employee, Salary; C. Marsolais, TaiMed: Commercial partner, Salary and Salary from Theratechnologies, commercial partner; S. Lewis, TaiMed: Employee, Salary and Salary from Theratechnologies, commercial partner